Mochtar Lubis and the 1969 Push for Spelling Unity in the Malay World - Febbrizal, Febbrizal; Abdurrakhman, Abdurrakhman (Analisis Sejarah, 2025)
This article examines the controversy surrounding standardized spellings for Malay languages, which share a common ancestry and historical ties across Indonesia and Malaysia. The issue was first publicly raised by Indonesian scholar and journalist Mochtar Lubis in 1969 through an article in the Harian Indonesia Raya daily newspaper, where Lubis later elaborated further in his role as editor-in-chief. This study is grounded in historical methodology and utilizes content analysis. Findings suggest that debates on spelling standardization stemmed from inconsistent usage of Indonesian orthography in educational and public settings. A written interview conducted by Lubis with Malaysian Prime Minister Tunku Abdul Rahman included discussions on spelling unification, which the Prime Minister supported. His response suggested the establishment of a conference and a linguistic research department comprising experts on languages spoken across both nations.